2019
DOI: 10.1016/j.bpj.2019.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Force-Dependent Facilitated Dissociation Can Generate Protein-DNA Catch Bonds

Abstract: Cellular structures are continually subjected to forces, which may serve as mechanical signals for cells through their effects on biomolecule interaction kinetics. Typically, molecular complexes interact via ''slip bonds,'' so applied forces accelerate off rates by reducing transition energy barriers. However, biomolecules with multiple dissociation pathways may have considerably more complicated force dependencies. This is the case for DNA-binding proteins that undergo ''facilitated dissociation,'' in which c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 111 publications
(225 reference statements)
0
10
0
Order By: Relevance
“…In contrast to an isolated VBS helix, which exists in a force-free environment, the mechanically exposed VBS in talin are under forces of several pN 12,13,16 , which may alter the conformation of the VBS helix significantly impacting on the binding affinity 29 and kinetics 30 . Hence, further studies on the force-dependent conformations of VBSs under a few pN forces and the resulting effects on the vinculin-talin VBS interaction may provide insight into this important linkage.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to an isolated VBS helix, which exists in a force-free environment, the mechanically exposed VBS in talin are under forces of several pN 12,13,16 , which may alter the conformation of the VBS helix significantly impacting on the binding affinity 29 and kinetics 30 . Hence, further studies on the force-dependent conformations of VBSs under a few pN forces and the resulting effects on the vinculin-talin VBS interaction may provide insight into this important linkage.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 50 simulations, we found that only 24 of the 𝑓 = 0.3 pN/s, 33 of the 𝑓 = 10 pN/s, and 5 of the 𝑓 = 30 pN/s simulated data sets were well-fit by equation (18b) (Table 4). * 𝑘 off,c-s (𝐹 = 0) = 𝑘 0,c + 𝑘 0,s = 1.05 per equation (17) for the parameters used in the simulation As we observed for the simulated data without accounting for the effect of experimental noise (Table 3), the cumulative distribution function-like analysis technique was able to resolve the catch-bond fitting parameters reasonably well (despite a 17%, P value = 0.02 two-tailed ttest, error in resolving the force sensitivity of the catch bond) with low s.e.m. of the fits in low loading rate simulations, and the slip-bond fitting parameters (despite a low number of well-fit data sets) in the high loading rate simulation (Table 4).…”
Section: Effect Of Experimental Noise On Catch-slip Bondsmentioning
confidence: 99%
“…We also discuss the implications of our results on using optical tweezers to collect force-dependent dissociation data.force 16 . Catch bonds have a lifetime that increases with applied force 10,17 . Ideal bonds have a 42 lifetime that is independent of applied force 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Slip bonds have a lifetime that decreases with the increasing applied force 16 . Catch bonds have a lifetime that increases with applied force 10,17 . Ideal bonds have a lifetime that is independent of applied force 10 .…”
Section: Introductionmentioning
confidence: 99%